Development of an Integrated Problem-Based Learning (PBL) Online-Based Learning Model to Improve the Feasibility and Effectiveness of Physics Learning - Sofvan; Herpratiwi; Fitri, Dina Martha (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study aimed to develop, validate, and evaluate the feasibility and effectiveness of a Google Sites–based e-Module integrated with the Problem-Based Learning (PBL) model in improving physics learning outcomes of Grade XII students on dynamic electricity material. A Research and Development (R&D) design following the Borg and Gall framework was employed, encompassing needs analysis, product design, development, expert validation, revision, and trial stages. Expert validation involved material, media, and design specialists. Feasibility was evaluated through small-group (n = 6) and large-group (n = 12) practicality trials using a five-point Likert-scale questionnaire. Effectiveness was measured via pre-test and post-test instruments, with improvement calculated using the normalized gain (N-Gain) formula. Instrument reliability was confirmed with Cronbach's Alpha values of 0.905 (pre-test) and 0.861 (post-test). Expert validation yielded average scores of 93.46% (material), 93.75% (media), and 86.50% (design), all classified as "very highly valid." Practicality trials produced average percentages of 93.75% (small group) and 92.97% (large group), both in the "excellent" category. Pre-test and post-test mean scores were 58.37 and 85.51, respectively, yielding an N-Gain of 0.65 (medium/moderately effective category). The Google Sites–based PBL-integrated e-Module is feasible, practical, and moderately effective for use in physics learning. Limitations include a small, single-school sample, a focus on one topic, and the absence of a control group; future research should employ comparative designs with larger, more diverse samples.